THE INFLUENCE OF BRAND AWARENESS AND BRAND ASSOCIATION ON THE REPURCHASE INTENTION OF ADIDAS SHOES IN SURABAYA CITY - Ramadani, Tri Prasetyo; Aminah, Siti (Yayasan Education and Social Center, 2024)
The development of the footwear industry in Indonesia is quite rapid in line with the development of the fashion industry in the global market, and is expected to continue to grow over the next few years. One shoe brand that is quite popular in Indonesia is the Adidas shoe brand. Adidas experienced its first loss in the last 30 years since 1992. The aim of this research is to determine the influence of Brand Awareness and Brand Association on Repurchase Intention for Adidas shoes in the city of Surabaya. This research applies quantitative research and variable measurements are carried out using a Likert scale. The sampling technique used non-probability sampling with accidental sampling technique with a sample size of 110 respondents. Meanwhile, the data analysis technique used is the component-based Structural Equation Modeling (SEM) method using the Partial Least Square (PLS) analysis tool. The research results show that Brand Awareness has a significant positive effect on Repurchase Intention. Brand Association has a significant positive effect on Repurchase Intention